2019
DOI: 10.3390/jcm8091302
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Disease Progression in Patients with Bicuspid Aortic Stenosis Using Mathematical Modeling

Abstract: We aimed to develop a mathematical model to predict the progression of aortic stenosis (AS) and aortic dilatation (AD) in bicuspid aortic valve patients. Bicuspid AS patients who underwent at least two serial echocardiograms from 2005 to 2017 were enrolled. Mathematical modeling was undertaken to assess (1) the non-linearity associated with the disease progression and (2) the importance of first visit echocardiogram in predicting the overall prognosis. Models were trained in 126 patients and validated in an ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
(37 reference statements)
0
6
0
Order By: Relevance
“…In our analysis, the rapid annual progression of the mean gradient was related to dyslipidemia, diabetes, BAV-LN morphotype, the presence of raphe and basal mean gradient. However, annual progression of the mean gradient is not linear and significantly related to the basal gradient [29] Similarly, progression of AR, in addition to the follow-up interval, was associated with hypertension, dyslipidemia, presence of raphe and basal AR. Michelena et al [7], in a community study, showed age, dyslipidemia and the presence of raphe to be associated with valve degeneration.…”
Section: Discussionmentioning
confidence: 82%
“…In our analysis, the rapid annual progression of the mean gradient was related to dyslipidemia, diabetes, BAV-LN morphotype, the presence of raphe and basal mean gradient. However, annual progression of the mean gradient is not linear and significantly related to the basal gradient [29] Similarly, progression of AR, in addition to the follow-up interval, was associated with hypertension, dyslipidemia, presence of raphe and basal AR. Michelena et al [7], in a community study, showed age, dyslipidemia and the presence of raphe to be associated with valve degeneration.…”
Section: Discussionmentioning
confidence: 82%
“…Recently, the diagnosis of normally functioning BAV in patients without valve dysfunction and aortopathy is increasing. There have been studies on factors that determine valve dysfunction in BAV patients ( 20 22 ) or progression in BAV patients with significant valvular dysfunction ( 4 ). Previous studies have also examined how these factors affect left ventricular diastolic function, according to BAV morphology ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is now wellestablished that initial severity is an important predictor of more rapid progression. 6,12,15 As a result, the confounding effect on progression rate introduced by differences in baseline severity between groups may bias the comparison.…”
Section: Discussionmentioning
confidence: 99%
“…However, in both the above studies, the BAV patients differed significantly from TAV patients in terms of baseline AS grade and hemodynamic parameters. It is now well‐established that initial severity is an important predictor of more rapid progression 6,12,15 . As a result, the confounding effect on progression rate introduced by differences in baseline severity between groups may bias the comparison.…”
Section: Discussionmentioning
confidence: 99%